Advancing Employee Retention through Compensation: Mediating Roles of Blue Ocean Leadership and Work Engagement in Human Capital Value among Gen Z - Alfy, Riadh; Janah Sojanah; Siregar, Alfi Syahrah; Ade Sobandi (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
This study examines the relationship between compensation and employee retention, with a focus on the mediating roles of Blue Ocean Leadership and Employee Work Engagement among Generation Z employees in West Java. Grounded in Social Exchange Theory, the research highlights how compensation influences retention directly and indirectly. Using Partial Least Squares-Structural Equation Modeling (PLS-SEM), data were collected from 217 respondents representing various industries. The results reveal that compensation has a significant positive impact on employee retention. Furthermore, Blue Ocean Leadership and Employee Work Engagement mediate this relationship, though their effects are relatively limited. The findings underscore the importance of integrating financial incentives with innovative leadership practices and engagement strategies to improve retention rates. Practical implications suggest that organizations should enhance compensation frameworks while fostering inclusive leadership and meaningful engagement initiatives. Future research should explore additional mediators and longitudinal impacts to deepen understanding of these dynamics.